Mass Mobilization and the Durability of New Democracies - Kadivar, Mohammad Ali (American sociological review, 2018)
The “elitist approach” to democratization contends that “democratic regimes that last have seldom, if ever, been instituted by mass popular actors” (Huntington 1984:212). This article subjects this observation to empirical scrutiny using statistical analyses of new democracies over the past half-century and a case study. Contrary to the elitist approach, I argue that new democracies growing out of mass mobilization are more likely to survive than are new democracies that were born amid quiescence. Survival analysis of 112 young democracies in 80 different countries based on original data shows that the longer the mobilization, the more likely the ensuing democracy is to survive. I use a case study of South Africa to investigate the mechanisms. I argue that sustained unarmed uprisings have generated the longest-lasting new democracies—largely because they are forced to develop an organizational structure, which provides a leadership cadre for the new regime, forges links between the government and society, and strengthens checks on the power of the post-transition government.